Pengaruh Model Pembelajaran Auditory Intellectually Repetition Berbantuan Wordwall Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Anis Ilyani; Nuraina Nuraina; Haves Qausar (FKIP Universitas Palangka Raya, 2025)
Students' critical thinking skills in mathematics are still relatively underdeveloped. This is because students tend to view problems from only one perspective, making them less able to evaluate and choose effective solutions. Therefore, innovative and diverse learning models are needed to develop this ability, one of which is the Auditory Intellectually Repetition (AIR) learning model. This study aims to determine the effect of using the AIR learning model with the help of word walls on students' mathematical critical thinking skills. This study is a quasi-experimental study with an unequal posttest-only control group design. The study population consisted of eighth-grade students at the UPTD of SMP Negeri 2 Gandapura. A saturated sampling technique was used, with class VIII-B as the experimental group and class VIII-A as the control group. Data were collected using a post-test to measure mathematical critical thinking skills. Data were analyzed using an independent sample t-test with the help of SPSS version 25 software, with a significance level set at 5%. The results of the analysis showed that the significance value (Sig. 2-tailed) was 0.028 < 0.05. Therefore, it can be concluded that the AIR learning model, which is supported by wordwall, has an influence on students' critical mathematical thinking skills in mathematics learning.